Measuring Efficiency Of Family And Non-Family Firm Amidst Covid-19 Times: Do They Perform Differently? - Hadi Wibowo; Adler Haymans Manurung; Roy Sembel; Erika Pritasari Wybawa (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The outbreak of COVID-19 pandemic in early 2020 has inflicted serious financial distresses for most firms in multi-sectoral industries. Each of them was enforced to deal with the economic downturns by working more efficiently. In this case, family and non-family firms might perform differently to protect themselves from bankruptcy. This research aims to measure firm efficiency by employing a total of 52 entities listed on Indonesia Stock Exchange (IDX), 26 entities for each type of firms from 2019 to 2022, reflecting the times before, during, and after the pandemic. At the first stage, date envelopment analysis (DEA) with constant return-to-scale (CRS) input-oriented approach is employed to generate deterministic efficiency scores of each sample which the bias is then corrected using Simar and Wilson’s bootstrap technique. At the second stage, hypothesis testing is conducted to examine whether the difference in efficiency score between both types of firms is significant. The result shows that family and non-family firms do not perform differently during a 4-year of research period (p-value=0.136). Nevertheless, family firms exhibit a significant drop in 2020 (p-value=0.0061), where this condition reversed with a significant increase in 2021 (p-value=0.0002). Non-family firms perform more stably throughout the research years. Finally this research may contribute to the development of organization-related science, business, and strategic management. The way most family firms operate might reflect the socio-cultural attributes of a nation. There is no other similar study found since COVID-19 pandemic is still considered as a relatively new global health crisis.